Comparison of post-operative complications in modified radical mastectomy patients with full suction and compression bandage versus half suction and non-compression bandage - Athar, Mohammad; Kala, Sanjay; Gupta, Abhineet; Varshney, Ashish (International Surgery Journal, 2020)
Background: Modified radical mastectomy still remains the most common surgical procedure employed in definitive management of breast cancer. Post mastectomy problems include skin flap necrosis, prolonged axillary drainage, seroma formation, wound gaping etc., among all seroma is commonest. Drainage usage and dressing applied after this procedure is debatable due to varying recommendations. Methods: A prospective randomized control trial was conducted on 84 FNAC/TRUECUT biopsy proven cases of early and locally advanced breast cancer patients admitted in surgery department, GSVM Medical College, Kanpur over a period of two years. Aiming to compare full suction drainage and compression dressing (n=42) (group 1) with half suction drainage and non-compression dressing (n=34) (group 2), in terms of post-operative morbidities like skin flap necrosis, prolonged axillary drainage, seroma formation, wound gaping and length of hospital stay. Romsons 16 number Romovac drains were used for suction and 2 elastic 6” crape bandage were used for compression. Results: During follow-up there was significant lower incidence of seroma formation in group 1 patients compared to group 2 patients (p<0.0019). Full compression dressing patients have increased incidence of superficial skin necrosis compared to non-compression dressing patients (p<0.022). Patients with half suction drainage and non-compression dressing has early drain removal than patients with full suction drainage and compression dressing (p<0.05), the length of hospital stay was less in group 2 compared to group 1. Conclusions: There is markedly lesser incidence of post-operative seroma formation along with reduced morbidity in the form of patients discomfort and flap necrosis in post MRM patients with full suction drainage and compression dressing, but it requires a greater hospital stay and has slightly higher risk of superficial skin necrosis which can be easily managed with topical ointments, compared to patients with half suction drainage and non-compression dressing.